2011
DOI: 10.1111/j.1440-1843.2011.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of epigenetics in the development of chronic obstructive pulmonary disease

Abstract: It is generally accepted that genetic predisposition plays a role in COPD development in susceptible individuals. Therefore, many candidate genes that could be linked to the development of disease have been examined in COPD. However, inconsistent results in different study populations often limit this approach, suggesting that not only genetics, but also other factors, may be contributed to the susceptibility to COPD. Epigenetic mechanisms can affect the transcriptional activity of specific genes, at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 95 publications
0
20
0
1
Order By: Relevance
“…What is becoming even more evident is the importance of epigenetic regulation in the future and retrospective lead search and optimization of therapies for these diseases [45][46][47][48][49][50]. Further functional studies are needed to determine if and how methylation within the pendrin promoter alters SLC26A4 gene expression, and in what context this type of epigenetic regulation has in pendrin-associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…What is becoming even more evident is the importance of epigenetic regulation in the future and retrospective lead search and optimization of therapies for these diseases [45][46][47][48][49][50]. Further functional studies are needed to determine if and how methylation within the pendrin promoter alters SLC26A4 gene expression, and in what context this type of epigenetic regulation has in pendrin-associated disease.…”
Section: Discussionmentioning
confidence: 99%
“…The CSE group mice were injected intraperitoneally with CSE at day 0, 11, 22 of the study, and injected with 0.3 mL PBS at day 15, 17, 19 of study. While the control group mice were administrated with 0.3 mL PBS in the same way at day 0, 11,15,17,19,22. The CSE þ AZA group was injected with intraperitoneally with 0.3 mL CSE at day 0, 11, 22, and AZA at day 15,17,19.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…17,18 Promoter methylation leads the condensation of chromatin into a compact state, which is inaccessible by transcription factors, causing a down-regulation of exon expression. 19 Recent studies also demonstrated the involvement of epigenetics in COPD, 19,20 and our previous study showed demethylation might protect models from emphysema. 21 Thus, the methylation-related apoptosis might play a role in emphysema pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…(34). SIRT1'in fosforilasyonunu inhibe eden yeni farmakolojik tedaviler KOAH'lı hastalarda inflamasyonu iyileştirebilir ancak steroid direncini düzeltmedeki etkileri henüz bilinmemektedir (35). KOAH'ta oksidatif stresle artan ve IL-1 tarafından uyarılan IL-6, IL-8 (KC) ekspresyonu bromodomain ve ekstraterminal proteinlerce (BET) baskılanarak antiinflamatuvar tedavi sağlanabileceği söylenmiştir (36).…”
Section: Sigara -Oksidatif Stresunclassified